Effect of ubiquitin-specific proteinase 43 on ovarian serous adenocarcinoma and its clinical significance - Qin Li; Wenhao Li; Jiahao Wang; Wenjing Shi; Taorong Wang (Journal of Obstetrics and Gynaecology)
Background Ovarian cancer stands as a highly aggressive malignancy. The core aim of this investigation is to uncover genes pivotal to the progression and prognosis of ovarian cancer, while delving deep into the intricate mechanisms that govern their impact.Methods The study entailed the retrieval of RNA-seq data and survival data from the XENA database. Outliers were meticulously excluded in accordance with TCGA guidelines and through principal components analysis. The R package ‘deseq2’ was harnessed to extract differentially expressed genes. WGCNA was employed to prioritise these genes, and Cox regression analysis and survival analysis based on disease-specific time were conducted to identify significant genes. Immunohistochemistry validation was undertaken to confirm the distinct expression of USP43. Furthermore, the influence of USP43 on the biological functions of ovarian cancer cells was explored using techniques such as RNA interference, western blotting, scratch assays, and matrigel invasion assays. The examination of immune infiltration was facilitated via CIBERSORT.Results The study unearthed 5195 differentially expressed genes between ovarian cancer and normal tissue, comprising 3416 up-regulated and 1779 down-regulated genes. WGCNA pinpointed 204 genes most intimately tied to tumorigenesis. The previously undisclosed gene USP43 exhibited heightened expression in tumour tissues and exhibited associations with overall survival and disease-specific survival. USP43 emerged as a driver of cell migration (43.27 ± 3.91% vs 19.69 ± 1.94%) and invasion ability (314 ± 32 vs 131 ± 12) through the mechanism of epithelial mesenchymal transition, potentially mediated by the KRAS pathway. USP43 was also identified as a booster of CD4+ T memory resting cell infiltration, while concurrently reducing M1 macrophages within cancer, thereby fostering a milieu with relatively immune suppressive traits. Interestingly, USP43 demonstrated connections with epigenetically regulated-mRNAsi, although not with mRNAsi.Conclusion This study underscores the role of USP43 in facilitating tumour migration and invasion. It postulates USP43 as a novel therapeutic target for ovarian cancer treatment.